2014
DOI: 10.1097/jcn.0b013e31827db5eb
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Cardiovascular Disease, Perceived Cardiovascular Disease Risk, and Health-Related Behavior

Abstract: Background Over 82 million Americans have one or more forms of cardiovascular disease (CVD), accounting for 32.8% of all deaths in the United States. Although the evidence for the familial aggregation of CVD is strong, the relationship between family history (FH) of CVD, perceived risk for CVD and their relationship to health-related behavior is poorly understood. Objective The objective of this article is to review and summarize the published research on the relationship between a FH of CVD, an individual’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
(122 reference statements)
3
59
0
1
Order By: Relevance
“…It was noted that GPR109A activation is required for antilipolytic activity. Thus, the structural feature of GPR109A as well as its binding with nicotinic acid Recently in 2010, 2-(trifluoromethyl)pyrido [2,3] pyrimidin-4(3)-one (3) possessing fused pyridine and pyrimidinone rings as a core structure was docked onto the human GPR109A receptor. The molecular docking result showed that nitrogen atoms in both pyridine and pyrimidinone rings interact with positively charged residue of arginine 111 in TMH3 of GPR109A as well as using the carbonyl group of pyrimidinone binds to hydroxyl group of serine 178 of ECL2 through hydrogen bonding [96].…”
Section: Drug Acting On Nicotinic Acid Receptormentioning
confidence: 97%
See 4 more Smart Citations
“…It was noted that GPR109A activation is required for antilipolytic activity. Thus, the structural feature of GPR109A as well as its binding with nicotinic acid Recently in 2010, 2-(trifluoromethyl)pyrido [2,3] pyrimidin-4(3)-one (3) possessing fused pyridine and pyrimidinone rings as a core structure was docked onto the human GPR109A receptor. The molecular docking result showed that nitrogen atoms in both pyridine and pyrimidinone rings interact with positively charged residue of arginine 111 in TMH3 of GPR109A as well as using the carbonyl group of pyrimidinone binds to hydroxyl group of serine 178 of ECL2 through hydrogen bonding [96].…”
Section: Drug Acting On Nicotinic Acid Receptormentioning
confidence: 97%
“…However, high in vitro clearance rate of the 2-(trifluoromethyl)pyrido pyrimidinone compound (3) was reported. In order to overcome this problem, the 2-trifluoromethyl (CF 3 ) group of compound 3 was optimized to achieve a new analog as 2-((4-fluorophenethoxy)methyl) pyrido [2,3] pyrimidin-4(3)-one (4) which exhibited both good binding activity and low microsomal clearance rate.…”
Section: Drug Acting On Nicotinic Acid Receptormentioning
confidence: 99%
See 3 more Smart Citations